Implementasi Steganografi LSB Dengan Enkripsi Vigenere Cipher Pada Citra - Laila, Niria; Sinaga, Anita Sindar RM (ScientiCO : Computer Science and Informatics Journal, 2018)
Message encoding is an art and science to maintain news or data, learn mathematical techniques related to aspects of information security such as data confidentiality, data validity, data integrity, and data authentication. The process of encoding and inserting messages with the Vigenere Cipher and LSB methods is the first step in inputting text and keyword files, then text files and keywords are converted into decimal numbers, then processed according to the Vigenere Cipher formula, the ciphertext is then transformed into binary form it is inserted into the image by means of each bit of the ciphertext in the last bit of the image, so it is expected that the data sent is not easy to read by third parties. The vigenere cipher algorithm and the LSB (Last Significant Bit) technique can be used as a solution for the security of secret messages that are inserted into the image, can be re-revealed exactly the same as the original form and do not experience the slightest damage.